All is good with the banana tree - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
It would be a mistake to let the banana overshadow the banana tree. For while the fruit lends itself to a variety of uses, the pseudostem and leaves can often also be made into innovative products. In the South, a number of countries are doing just that.